Chemoentrepreneurship with Cooperative Integrated Process Inquiry Strategy to Increase Students' Entrepreneurial Interest and Learning Motivation - Sumarti, S. S.; Aris, S. R. S.; Aini, R. N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Colloid chemistry learning at SMAN 1 Mijen Demak had a less useful impact as it has not integrated the process of making with the products needed in everyday life. The lesson also did not equip students with the skills in entering the entrepreneurship world. The observation results indicated that the XI IPA1 grade students in SMAN 1 Mijen Demak had low entrepreneurial interest and motivation. This was due to the tedious and less-motivated chemistry learning. Therefore, this study aimed to increase the students' entrepreneurial interest and learning motivation on colloid materials through Integrated Cooperative Inquiry Process strategy. A classroom action research applied in this research consisted of three cycles. Each cycle had several stages which were planning, implementation, observation, and reflection. The data on the students’ entrepreneurial interest and learning motivation were collected through observation and questionnaire. The descriptive analysis was adopted in this research. The data were analysed using the average mastery and proportion. Based on the analysis of cycles I, II and III, the percentage of the students’ entrepreneurship interest increased from 47.64% to 51.17%; 72,16% and 81,10% having 38 students achieved the mastery learning. While the learning motivation increased from 49.55% to 56.08%; 68.21% and 76.32% having 37 students reached the mastery learning. It concluded that the CIPI (Cooperative Integrated Process Inquiry) with CEP (Chemo entrepreneurship) approach could increase the students’ entrepreneurial interest and learning motivation.